2015
DOI: 10.1074/jbc.m114.609305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FAH Domain-containing Protein 1 (FAHD1) as Oxaloacetate Decarboxylase

Abstract: Background: Enzymes of the FAH superfamily catalyze a multitude of diverse chemical reactions. Results: Using molecular modeling followed by biochemical investigations, FAHD1 was identified as oxaloacetate decarboxylase. Conclusion: Our findings suggest that ODx activity can be found in eukaryotic members of the FAH superfamily. Significance: Our results identify a mammalian ODx enzyme as a so far undescribed player in mitochondrial metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 21 publications
0
48
0
Order By: Relevance
“…(A) ODx activity of mFAHD1: within the accuracy of a photometric assay [7], v max ranges from 0.18 to 0.24 μmol/min/mg, and K M ranges from 8 to 78.0 μM, similar to hFAHD1 [6,23]. Within the given range, our best-model fit found v max = 0.21 μmol/min/mg and K M = 42.8 μM (see Table 2).…”
Section: Figure 4 Michaelis-menten Kinetics Of Odx and Aph Activitiementioning
confidence: 74%
See 2 more Smart Citations
“…(A) ODx activity of mFAHD1: within the accuracy of a photometric assay [7], v max ranges from 0.18 to 0.24 μmol/min/mg, and K M ranges from 8 to 78.0 μM, similar to hFAHD1 [6,23]. Within the given range, our best-model fit found v max = 0.21 μmol/min/mg and K M = 42.8 μM (see Table 2).…”
Section: Figure 4 Michaelis-menten Kinetics Of Odx and Aph Activitiementioning
confidence: 74%
“…Polyclonal antisera against FAHD1 were raised against recombinant untagged hFAHD1 protein and His6/S-doubl e-tagged mFAHD1 protein, both produced in E. coli [23]. Recombinant protein was purified from E. coli using a series of three subsequent chromatographic steps as described [7,23]. Approximately 4 mg of pure recombinant protein was used by a commercial supplier (Biogenes, Berlin, Germany) to produce specific antisera which were shipped to our laboratory.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study to further investigate the cellular role of FAHD1, molecular modeling was applied to search for a close structural match between the catalytic domain of FAHD1 and other members of the FAH family [9]. This process yielded the prokaryotic enzyme Cg1458 as a promising candidate, previously identified as a soluble ODx [2].Subsequent in vitro analysis of purified recombinant human FAHD1 confirmed that it indeed exhibits ODx activity.…”
Section: Editorialmentioning
confidence: 99%
“…It can be expected that studies with available FAHD1-/-mice [9] will shed light on the enigmatic role of the newly identified ODx FAHD1 and help to elucidate its functional interaction with other metabolic pathways. Fumarylacetoacetate hydrolase (FAH) domain-containing protein 1 (FAHD1) is found to play a key role in central metabolism, in particular at the intersection of catabolic pathways and the tricarboxylic acid cycle (TCA).…”
mentioning
confidence: 99%